2009
DOI: 10.9795/bullgsj.60.105
|View full text |Cite
|
Sign up to set email alerts
|

Geological interpretation of groundwater level lowering in the North China Plain

Abstract: Groundwater level lowering in the North China Plain (NCP) has been developing during past several decades by overuse in populated cities and industrial districts as well as by irrigation. To interpret groundwater level lowering in terms of aquifer-bearing beds having relatively high porosity, contour maps and cross sections of water level lowering based on monitoring data are compared with subsurface Quaternary geologic map. The comparison revealed that the extents of productive shallow and deep aquifers are g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 4 publications
1
36
0
Order By: Relevance
“…One of the main reasons for this difference is that the GBCNP-based estimate includes only groundwater information in shallow aquifers of China northern plains, whereas the GRACE observes all GWS changes from all aquifers. Some studies have shown that the deep groundwater table is also decreased greatly in the piedmont region of the Taihang Mountains and the central plain region of the Hebei province [World Bank, 2001;Foster et al, 2004;Tamanyu et al, 2009]. The high-groundwater depletion rate estimated using GRACE data indicates the important contribution of groundwater depletion in deep aquifers of North China.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main reasons for this difference is that the GBCNP-based estimate includes only groundwater information in shallow aquifers of China northern plains, whereas the GRACE observes all GWS changes from all aquifers. Some studies have shown that the deep groundwater table is also decreased greatly in the piedmont region of the Taihang Mountains and the central plain region of the Hebei province [World Bank, 2001;Foster et al, 2004;Tamanyu et al, 2009]. The high-groundwater depletion rate estimated using GRACE data indicates the important contribution of groundwater depletion in deep aquifers of North China.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in the study area, storage gain in soil moisture is sustained by storage loss in groundwater (Yang et al, 2002(Yang et al, , 2003Moiwo et al, 2010;Hu et al, 2010). Saturated storage loss in the basin is estimated at 1.5-2.0 m/yr (Yang et al, 2002;Foster et al, 2004;Tamanyu et al, 2009;Hu et al, 2010). While a portion of the storage loss goes to augment soil moisture storage, another portion of it is lost to ET (Yang et al, 2006.…”
Section: Precipitation and Evapotranspirationmentioning
confidence: 94%
“…In the basin, Quaternary-aged aquifers of inter-fingering gravels, sands and silts extend to over 400 m beneath surface alluvial fans (Foster et al, 2004;Tamanyu et al, 2009). Although the groundwater is largely stored in bicarbonate (Fei, 1998) (Tamanyu et al, 2009), recharge is highest in the coarse deposits of the foothill corridor (Yang et al, 2002;Han et al, 2008, in press).…”
Section: Agro-hydrologymentioning
confidence: 99%
See 2 more Smart Citations